Therapeutic effect of pirfenidone in the sugen/hypoxia rat model of severe pulmonary hypertension. Issue 3 (27th November 2018) - Poble, Paul-Benoit; Phan, Carole; Quatremare, Timothée; Bordenave, Jennifer; Thuillet, Raphaël; Cumont, Amélie; Huertas, Alice; Tu, Ly; Dorfmüller, Peter; Humbert, Marc; Ghigna, Maria-Rosa; Savale, Laurent; et al.
ABSTRACT: Heightened pulmonary artery smooth muscle cell (PA‐SMC) proliferation and migration and dynamic remodeling of the extracellular matrix are hallmark pathogenic features of pulmonary arterial hypertension (PAH). Pirfenidone (PFD) is an orally bioavailable pyridone derivative with antifibrotic, antiinflammatory, and antioxidative properties currently used in the treatment of idiopathic pulmonary fibrosis. We therefore evaluated the efficacy of curative treatments with PFD in the sugen/hypoxia (SuHx) rat model of severe pulmonary hypertension. Treatment with PFD (30 mg/kg per day by mouth 3 times a day for 3 wk) started 5 wk after sugen injection partially reversed established pulmonary hypertension, reducing total pulmonary vascular resistance and remodeling. Consistent with these observations, we found that continued PFD treatment decreases PA‐SMC proliferation and levels of extracellular matrix deposition in lungs and right ventricles in SuHx rats. Importantly, PFD attenuated the proproliferative and promigratory potentials of cultured PA‐SMCs from patients with idiopathic PAH and their capacity to produce extracellular matrix components. Finally, we found that PFD dose dependently enhanced forkhead box Ol protein levels and its nuclear translocation in cultured idiopathic PAH PA‐SMCs and in PFD‐treated SuHx rats. PFD appears to be a potential therapy for PAH worthy of investigation and evaluation for clinical use in conjunction with current PAH treatments.—Poble, P.‐B., Phan, C., Quatremare, T., Bordenave, J., Thuillet, R., Cumont, A., Huertas, A., Tu, L., Dorf muller, P., Humbert, M., Ghigna, M.‐R., Savale, L., Guignabert, C. Therapeutic effect of pirfenidone in the sugen/hypoxia rat model of severe pulmonary hypertension. FASEB J. 33, 3670–3679 (2019). www.fasebj.org